2018
DOI: 10.21873/anticanres.12676
|View full text |Cite
|
Sign up to set email alerts
|

CC-Chemokine Ligand 18 Is an Independent Prognostic Marker in Lymph Node-positive Non-small Cell Lung Cancer

Abstract: In advanced lung adenocarcinoma, infiltration of CCL18 TAMs was increased and higher expression of CCL18 by TAMs was associated with a favorable prognosis in lymph-node positive NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…An increased level of CCL18 in colorectal cancer [43] and gastric adenocarcinoma [44] is associated with a better prognosis. In non-small cell lung cancer, a greater infiltration of CCL18-producing cells is associated with a better prognosis [183], although the level of this chemokine in the plasma of patients with this type of cancer is associated with a worse prognosis [175] (Table 1). Nevertheless, the data in the Human Protein Atlas (https://www.proteinatlas.org) on the level of mRNA for CCL18 in tumors of various cancers do not confirm a clear relationship between an increased CCL18 expression and a worse survival [184,185] (Table 2).…”
Section: Ccl18 As a Tumor Markermentioning
confidence: 99%
“…An increased level of CCL18 in colorectal cancer [43] and gastric adenocarcinoma [44] is associated with a better prognosis. In non-small cell lung cancer, a greater infiltration of CCL18-producing cells is associated with a better prognosis [183], although the level of this chemokine in the plasma of patients with this type of cancer is associated with a worse prognosis [175] (Table 1). Nevertheless, the data in the Human Protein Atlas (https://www.proteinatlas.org) on the level of mRNA for CCL18 in tumors of various cancers do not confirm a clear relationship between an increased CCL18 expression and a worse survival [184,185] (Table 2).…”
Section: Ccl18 As a Tumor Markermentioning
confidence: 99%
“…An increased level of CCL18 in colorectal cancer and gastric adenocarcinoma is associated with a better prognosis. In non-small cell lung cancer, a greater infiltration of CCL18-producing cells is associated with a better prognosis [52], although the level of this chemokine in the plasma of patients with this type of cancer is associated with a worse prognosis. Since CCL18 has been demonstrated to be released by TAMs which play important roles in malignant diseases, CCL18 has been increasingly considered to be involved in the pathogenesis and progress of various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, the chemokine CCL18 ligand is highly expressed in M2 macrophages. Schmid et al 84 showed that a higher proportion of TAMs positives to CCL18 was related to a shorter survival rate by survival analysis; thus, this chemokine could be used as a prognosis biomarker. Schmid et al 85 showed that elevated CCL18 levels are related to tumor size and poor prognosis in the NSCLC tumor microenvironment; moreover, this work also highlighted that serum levels of CCL18 were not related to either tumor size or prognosis.…”
Section: Immunological Approach and Biomarkers For Cancer Diseasementioning
confidence: 99%